Presenting features and treatment of small intestinal adenomyosis in children: a 10-year retrospective study - Wang, Huan-sheng; Huang, Ke-hua; Jiang, Ren-sen; Lao, Jin; Long, Jie-xing; Wu, Miao-bing; Tang, Jia-lin; Jiang, Xian-ping; Wang, Bin; Chen, Zi-min; Wang, Jian-yao (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to analyze and summarize the clinical characteristics of small intestinal adenomyosis.MethodsA retrospective study was conducted on children with small intestinal adenomyosis at our center from 2014 to 2024. The age of onset, gender, clinical symptoms, auxiliary examination results, treatment plans, and pathological characteristics of the tumors were recorded and analyzed.ResultsSix cases of small intestinal adenomyosis were analyzed. The male-to-female ratio was 5:1. The median age was 19 months, with two-thirds of the affected children being under 2 years old. Two cases were identified in newborns during the treatment of intestinal malrotation. The remaining patients developed symptoms of intussusception. Preoperative ultrasound identified pathological lead points in two cases. Among the six cases, one case's adenomyoma was located in the jejunum, while the rest was located in the ileum, with tumors ranging from 25 to 140 cm from the ileocecal region. All six patients underwent resection of the tumor segments in the small intestine followed by anastomosis; postoperative prognosis was favorable. Of the six pathological results, glandular-like structures were found in five tumors, with three cases lined with cuboidal or columnar epithelium and one case lined with stratified or squamous epithelium.ConclusionsSmall intestinal adenomyosis is observed to be more prevalent in male, with onset ages ranging from six days to four years. It frequently coexists with recurrent intussusception, making reduction with air or water enema challenging. Abdominal ultrasound typically shows tumors at the leading edge of the intussusception, with compromised blood flow signals and multiple small cystic or honeycomb-like anechoic structures. Surgery is the primary treatment and generally results in a favorable prognosis.